Knowledge and Attitudes toward Human Papillomavirus and Human Papillomavirus-Vaccine Acceptance among Females in Saudi Arabia (Asian Journal of Pharmaceutics (AJP), 2025)
Human papillomavirus (HPV) poses significant health risks globally, being a primary cause of cervicalcancer (CC) and other malignancies. CC remains a leading cause of morbidity and mortality among women in Saudi Arabia,with an incidence rate of 1.9/100,000 women. Previous studies have indicated a general lack of awareness surroundingHPV and its vaccine among the Saudi population. Objective: This study aimed to assess knowledge, awareness, andHPV vaccine acceptance among females in Saudi Arabia. Methods: A cross-sectional study was conducted from July2024 to March 2025, enrolling Saudi females aged 12 years and older through questionnaires. A total of 798 participantswere included, comprising both medical professionals and the general public. Variables of interest included demographicinformation, knowledge levels regarding HPV, and attitudes toward HPV vaccination. Results: Among participants, 74.7%reported awareness of HPV, with the internet being the most referenced information source (37.1%). However, significantgaps were identified: 50.6% were unaware that HPV can be asymptomatic, and 60.2% lacked knowledge regarding itsassociation with various cancers. Only 3.3% had undergone HPV testing, while 48% recognized the vaccine’s potential toprevent CC and genital warts. Notably, 69.2% expressed willingness to receive the vaccine if offered for free, and 83.7%supported educational interventions to enhance awareness. Knowledge levels correlated significantly with age, education,and income, with 37.8% demonstrating low knowledge levels and only 34.1% showing high knowledge regardingHPV. Conclusion: The study reveals a mixed understanding of HPV and its vaccine among Saudi women, highlightingsignificant gaps in knowledge despite a generally positive attitude toward vaccination. Enhanced educational outreach andtargeted interventions are crucial to improve awareness and acceptance of the HPV vaccine, thereby supporting publichealth initiatives aimed at reducing HPV-related disease incidence.